Sustainable Supply Chain Management at Clif Bar - Sakyi, Kwesi Atta (Advances in Social Sciences Research Journal, 2019)
This paper has the objective of discussing the concept of sustainability by examining the practice in a case study of Clif Bar, a US-based company that deals in manufacturing nutritional foods for sports people, and whose model is outsourcing their core activities from upstream through mid-stream to downstream to small-scale farmers, cooperatives, and suppliers in the supply chain. The methodology adopted is that of review of secondary sources for analysis and insight. The concepts of sustainability and corporate social responsibility are discussed theoretically and practically in relationship to Clif Bar. The paper concludes that undertaking sustainability measures and corporate social responsibility may be costly in the short-run but highly beneficial to all in the long-run. It requires a multidisciplinary approach with a team comprising employees from diversified backgrounds.